2015
DOI: 10.1007/s10762-015-0159-3
|View full text |Cite
|
Sign up to set email alerts
|

A-189 dBc/Hz FoMT Wide Tuning Range VCO Using Q-Factor Enhancement Technique

Abstract: A 28-GHz voltage-controlled oscillator (VCO) with a wide tuning range and a low phase noise is presented in this paper. A PMOS-only cross-coupled pair with a lower flicker noise is exploited to provide the negative resistance. The mechanisms for enhancing the Qfactor of the LC tank at millimeter-wave (mm-wave) frequencies are analyzed and applied to optimize the proposed VCO design to obtain a low phase noise. To guarantee accurate oscillating frequencies, distributed interconnections are carefully modeled by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The study [26] found that when blood Tacrolimus concentration is greater than 20 μg •L-1, drug toxic side effects are prone to happen. Li J et al [27] reported that a male patient developed abdominal pain, digestive tract ul-cer and blindness in the right eye while maintaining high Fk506 blood concentration, and the symptoms were relieved after reduc-ing the drug concentration.…”
Section: Excess Dose Of Tacrolimusmentioning
confidence: 99%
“…The study [26] found that when blood Tacrolimus concentration is greater than 20 μg •L-1, drug toxic side effects are prone to happen. Li J et al [27] reported that a male patient developed abdominal pain, digestive tract ul-cer and blindness in the right eye while maintaining high Fk506 blood concentration, and the symptoms were relieved after reduc-ing the drug concentration.…”
Section: Excess Dose Of Tacrolimusmentioning
confidence: 99%